Maintenance management of external wall cladding in high rise building / Mohd Fauzi Mesoven - Mesoven, Mohd Fauzi (Faculty of Architecture, Planning and Surveying, 2010)
For high rise building construction, use cladding wall already currently popular now a day. Mostly wall cladding at high rise building very popular because the design very flexible, light, easy to install and most important it easy for maintenance. Cladding wall usage is for high-rise commercial, industrial, residential buildings, shopping malls, etc. Maintenance Management is an orderly and systematic approach to planning, organizing, monitoring and evaluating maintenance activities and their costs. Therefore the objective of this research are study on the type of maintenance management for external wall cladding, compare the building form and the method and equipment for doing the cleaning on high-rise building. The case study has been choosing in Kuala Lumpur and Selangor. To support this research, the structure interview will be made. The data has been collected from the observation, interview question and interview. The analysis is about the case study of maintenance management of external wall cladding on high-rise building. From the study, maintenance management of external wall cladding on high-rise building should be taking seriously. If the maintenance management is poor, it give big impact and effect to the value and image of the building. The building has deferent maintenance management for doing the cleaning depend on the size of building, building form and the most important aspect is the budget.